THE ROLE OF MULTIMEDIA LEARNING IN REDUCING MATH ANXIETY TO IMPROVE STUDENTS' MATHEMATICAL ABILITIES - Susilawati, Sumarni; Gunawan, Resky Nuralisa (Sora Journal of Mathematics Education, 2024)
Mathematics is an abstract theory, which causes many students to experience difficulties in learning it, leading to the emergence of math anxiety. This math anxiety affects students' attitudes and performance in mathematics. To reduce this issue, it is necessary to design learning that is enjoyable and motivating for students in mathematics education. Learning that utilizes digital technology provides a solution to reduce math anxiety. Students feel happy learning with interactive multimedia. Through multimedia, they can apply and solve problems using the theories they have learned. The use of technology in mathematics learning helps students achieve better results, enhances interaction and participation in learning, and offers significant opportunities to improve their learning experience.